The relationship between perceptions of shared decision‐making and patient‐reported outcomes in a cross‐sectional cohort of haemorrhoidectomy patients. (21st January 2022) - Merali, Khalil; Karimuddin, Ahmer; Crump, Trafford; Brown, Carl; Phang, Terry; Raval, Manoj; Liu, Guiping; Sutherland, Jason M.
Abstract: Aim: Shared decision‐making between patients and clinicians is important to surgical practice and patients' perceptions of their healthcare experience. This study aims to measure associations between patients' perceptions of their shared decision‐making (SDM) process and health‐related quality of life among a cohort of patients choosing surgical management of an elective surgical procedure, haemorrhoidectomy. Methods: This study is a single‐site study based in Vancouver, Canada. Consecutive patients of five colorectal surgeons registered for elective haemorrhoidectomy between September 2016 and June 2020 were eligible to participate. Participants completed the CollaboRATE instrument which measures patients' perceptions of their SDM after the surgical consultation, along with a number of other patient‐reported outcomes. Results: The participation rate was 45.3%, with 157 patients scheduled for haemorrhoidectomy providing complete information. Unadjusted results found that participants having the most comorbidities reported better communication with their surgeon. The adjusted results show that socioeconomic status and depression were associated with lower CollaboRATE scores. There was no effect of sex, pain interference, anxiety or perceived health status on participants' CollaboRATE scores. Conclusion: This study found evidence that participants with lower economic status or those reporting depressive symptoms had worse perceptions of their SDM process with their surgeon. These findings suggest that special attention should be paid to the surgical decision‐making process for these patient populations.